New Insights Into PTBP3 in Human Cancers: Immune Cell Infiltration, TMB, MSI, PDCD1 and m6A Markers - Fang, Zhen; Li, Peijuan; Li, Han; Chong, Wei; Li, Leping; Shang, Liang; Li, Fei (Frontiers in Pharmacology, 2022)
Polypyrimidine tract binding protein 3 (PTBP3) plays a critical role in post-transcriptional regulation. The role of PTBP3 in various human tumours was explored and analysed in this study based on the Cancer Genome Atlas and Gene Expression Omnibus datasets. PTBP3 was highly expressed in most tumours, such as breast invasive carcinoma, colon adenocarcinoma and hepatocellular carcinoma. PTBP3 overexpression generally predicts poor overall survival and disease-free survival in patients with adrenocortical carcinoma, lung squamous cell carcinoma, and pancreatic adenocarcinoma. However, low PTBP3 expression predicts poor prognosis in kidney renal clear cell carcinoma. We also explored PTBP3 genetic alterations in different tumour tissues. The result found that the frequency of PTBP3 alteration (>4%) was the highest in uterine tumours with “mutation” as the primary type. Furthermore, we found a significant correlation between PTBP3 expression and tumour mutational burden and microsatellite instability in various human tumours, and found that PTBP3 expression was positively correlated with TMB in ACC, STAD, PAAD, LUAD, and SARC. Two enhanced phosphorylation levels of S30 and S426 in colon cancer, ovarian cancer, and uterine corpus endometrial carcinoma were found. Further analysis indicated that PTBP3 expression was positively correlated with the cancer-associated fibroblasts for most tumour types. This study also found a relationship between immune checkpoints and N6-methyladenosine-related markers and PTBP3 expression. Moreover, the “mRNA surveillance pathway” and “RNA degradation” were involved in the functional mechanisms of PTBP3. These results provide new insights for molecular studies, and integrative analysis provided a framework for determining the predictive, prognostic, and therapeutic relevance of PTBP3 in cancer patients.